A Partnership Approach for Electronic Data Capture in Small-Scale Clinical Trials - Franklin, Joshua D. (2011)
Amid researchers’ growing need for study data management, the CTSA-funded Institute for Translational Health Sciences developed an approach to combine technical and scientific resources with small-scale clinical trials researchers in order to make Electronic Data Capture more efficient. In a 2-year qualitative evaluation we found that the importance of ease of use and training materials outweighed number of features and functionality. EDC systems we evaluated were Catalyst Web Tools, OpenClinica and REDCap. We also found that two other systems, Caisis and LabKey, did not meet the specific user needs of the study group.